Heterogeneity of psychosocial functioning in patients with bipolar disorder: Associations with sociodemographic, clinical, neurocognitive and biochemical variables - Ba, Zhengling; Chen, Minhua; Lai, Jiulan; Liao, Yingtao; Fang, Hengying; Lu, Dali; Zheng, Yingjun; Zong, Kunlun; Lin, Xiaoling (Frontiers in Psychiatry, 2022)
Objective: This study aims to identify the functional heterogeneity in fully or partially remitted patients with bipolar disorder (BD) and explore the correlations between psychosocial functioning and sociodemographic, clinical, neurocognitive and biochemical variables. Methods: One hundred and forty fully or partially remitted patients with BD and seventy healthy controls were recruited. Patients with BD were grouped into different profiles based on the Functioning Assessment Short Test (FAST) domain scores by hierarchical cluster analysis (HCA). The characteristics of functional subgroups and the correlations between psychosocial functioning and sociodemographic, clinical, neurocognitive and biochemical variables in each cluster were then analysed. Results: There were three functional profiles in patients with BD: the lower functioning group (LF), performed global functioning impairments; the moderate functioning group (MF), presented selective impairments in functional domains; and the good functioning subgroup (GF), performed almost intact functioning. Several variables including age, depressive symptoms, age at onset, suicidal ideation, visual reproduction test scores and some biochemical indexes (albumin, high-density lipoprotein cholesterol, total protein and serum total thyroxine) presented differently among these three functional subgroups. Conclusions: The characteristics of discrete subgroups and the specific clinical factors, neurocognitive domains and biochemical indexes that are correlated with specific functional subgroups will allow for making tailored interventions to promote the functional recovery and improve the quality of life.